2017
DOI: 10.12740/pp/onlinefirst/61352
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment and traits of autism in children

Abstract: Visual impairment present from birth or from an early childhood may lead to psychosocial and emotional disorders. 11-40% of children in the group with visual impairment show traits of autism. The aim of this paper was to present the selected examples of how visual impairment in children is related to the occurrence of autism and to describe the available tools for diagnosing autism in children with visual impairment. So far the relation between visual impairment in children and autism has not been sufficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…The variety of visual phenotypes reported in the literature may be due to the fact that ASD is a spectrum disorder, in which the severity and presentations of the symptoms vary over a very large range. Additionally, there have been many challenges in measuring visual function (including spatial acuity and contrast sensitivity) in this population, especially in children, because of wide variations in testing methods, sample sizes, selection of high‐functioning participants, cooperativeness during visual testing, and social and communication difficulties 12 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variety of visual phenotypes reported in the literature may be due to the fact that ASD is a spectrum disorder, in which the severity and presentations of the symptoms vary over a very large range. Additionally, there have been many challenges in measuring visual function (including spatial acuity and contrast sensitivity) in this population, especially in children, because of wide variations in testing methods, sample sizes, selection of high‐functioning participants, cooperativeness during visual testing, and social and communication difficulties 12 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Atypical visual processing can cause an individual to miss important social cues, such as eye contact and nuances in facial expression or skin pigmentation, and ultimately can have deleterious effects on the learning and acquisition of social skills 8 11 . Clinically, atypical visual phenotypes are common in ASD patients 12 14 , and many studies have reported a preference towards intricate details of a visual scene (“local details”) in ASD, as opposed to a contextual understanding of the image as a whole (“global structure”). It has been hypothesized that these phenotypes might be due to alterations in neural processing of spatial vision, or to a relatively increased response to information of high spatial frequencies 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…While autistic individuals predictably presented more autistic traits compared to TD and CVI individuals, the latter group also presented some autistic traits as measured by the AQ score. This is in line with an extensive literature showing that individuals with CVI present atypical behaviours often overlapping with autistic features, including communication difficulties, as well as repetitive behaviours and stereotyped patterns (Bathelt, Dale, & de Haan, 2017; Bathelt, de Haan, Salt, & Dale, 2018; Butchart et al ., 2017; Ek, Fernell, Jacobson, & Gillberg, 1998; Hobson & Lee, 2010; Jure, Pogonza, & Rapin, 2016; Kiani et al ., 2019; Mukaddes, Kilincaslan, Kucukyazici, Sevketoglu, & Tuncer, 2007; Wrzesinska, Kapias, Nowakowska‐Domagala, & Kocur, 2017). However, the AQ score in individuals with CVI may not reflect a real autistic behaviour but might be due to some specific questions closely related to visual skills, including visual imagery, attention to detail and patterns.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been noted that young persons with VI are more engaged in passive leisure activities than those without disabilities, and usually spend less time with their peers [33]. This may be attributed to the fact that young persons with VI are more prone to social isolation due to the limited opportunities for them to learn social skills by observing interactions in different contexts [34,35]. On the other hand, students with VI tend to be more engaged in peer contact through new media, thus compensating for the perceived traditional offline social isolation [19]; this could be reflected in the longer amounts of time spent playing games at the weekend.…”
Section: Discussionmentioning
confidence: 99%